2011
DOI: 10.1073/pnas.1110286108
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating hormone induces a Wnt-dependent, feed-forward loop for osteoblastogenesis in embryonic stem cell cultures

Abstract: We have shown that the anterior pituitary hormone, thyroidstimulating hormone (TSH), can bypass the thyroid to exert a direct protective effect on the skeleton. Thus, we have suggested that a low TSH level may contribute to the bone loss of hyperthyroidism that has been attributed traditionally to high thyroid hormone levels. Earlier mouse genetic, cell-based, and clinical studies together have established that TSH inhibits osteoclastic bone resorption. However, the direct influence of TSH on the osteoblast ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…While it inhibits osteoblastogenesis in bone marrow-derived cell cultures, TSH stimulates differentiation and mineralization in murine cell cultures through a Wnt5a-dependent mechanism [67]. Likewise, in vivo, intermittently administered TSH is anabolic in both rats and mice [69,73].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it inhibits osteoblastogenesis in bone marrow-derived cell cultures, TSH stimulates differentiation and mineralization in murine cell cultures through a Wnt5a-dependent mechanism [67]. Likewise, in vivo, intermittently administered TSH is anabolic in both rats and mice [69,73].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…At least 20 clinical studies have since documented tight and highly reproducible correlations between low TSH levels, bone loss, bone geometry, and fracture risk in patient cohorts across the globe . Evidence also shows that TSH protects the skeleton by exerting anti-resorptive and anabolic actions in rodent models and in people [37,[62][63][64][65][66][67][68][69][70][71].…”
Section: Thyroid Stimulating Hormonementioning
confidence: 99%
“…Activation of the TSH receptor (TSHR) on the osteoclast prevents the resorption of bone (4). When administered intermittently, TSH stimulates osteoblastic bone formation and, in rodent models, rescues ovariectomy-induced bone loss (5)(6)(7)(8). In contrast, absence of the TSHR in the global Tshr -/-mouse causes high-turnover osteoporosis (4).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that, in addition to its known function in stimulating thyroid follicular cells, TSH can act directly on the skeleton (4)(5)(6)(7)(8). Activation of the TSH receptor (TSHR) on the osteoclast prevents the resorption of bone (4).…”
Section: Introductionmentioning
confidence: 99%
“…While it inhibits osteoblastic differentiations in bone marrow-derived mesenchymal stromal cell cultures, TSH stimulates differentiation and mineralization in murine cell cultures via a Wnt5a-dependent manner. 12) Similarly, intermittently administered TSH showed anabolic effects on bone remodeling in both rats and mice. 13,14) Thus, the effect of TSH may be differentiation according to the differentiation stages.…”
Section: )mentioning
confidence: 99%